PENERAPAN TEACHING AT THE RIGHT LEVEL (TaRL) BERBANTUAN E-LKPD UNTUK MENINGKATKAN MOTIVASI BELAJAR MATEMATIKA SISWA KELAS VIII.I SMP NEGERI 1 KUTA UTARA - Ni Putu Diah Apriyantini; I Komang Sukendra (LP3M Universitas PGRI Mahadewa Indonesia, 2023)
Teaching at the Right Level (TaRL) learning is a teaching approach that focuses on student learning readiness, not just at the class level. The TaRL approach provides latitude or flexibility in teaching according to students' abilities. Students are not tied to grade levels, but are adjusted based on the abilities of the same students. The purpose of this study was to find out whether the application of Teaching at the Right Level (TaRL) assisted by E-LKPD can increase students' motivation to learn mathematics. This type of research is Classroom Action Research. The subjects of this research were class VIII.I students of SMP Negeri 1 Kuta Utara for the academic year 2022/2023 and the object of this study was students' motivation to learn mathematics. In this research through two cycles consisting of four stages of the activity process which includes (1) planning, (2) action, (3) observation, and (4) evaluation and reflection. Data collection techniques using non-test techniques, observation techniques, and interview techniques. The results of the study show that the application of Teaching at the Right Level (TaRL) learning with the help of E-LKPD can increase students' motivation to learn mathematics in class VIII.2 students of SMP Negeri 6 Denpasar in the 2022/2023 academic year.